Pendidikan karakter: menanamkan nilai-nilai positif pada generasi muda - Faizal Hasbi; Ine Indiyani; Muhammad Hafiz; Chanifudin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Character education plays a crucial role in shaping the younger generation to become individuals with integrity, strong morality, and ethical awareness. This article discusses the urgency of instilling positive values such as honesty, responsibility, empathy, respect, and discipline within educational settings. The integration of these values into elementary and secondary school curricula through a comprehensive and continuous approach can foster an environment that supports optimal character development. Schools are not only responsible for academic achievement but also for nurturing students’ personal growth and social responsibility.Various methods can be implemented to strengthen character education, including project-based learning, collaborative activities, extracurricular programs, and the consistent exemplary behavior demonstrated by educators and school staff. These approaches help students to experience and internalize values in real-life contexts. However, the implementation of character education often faces challenges, such as limited resources, lack of teacher training, and inconsistencies between school and home environments. Therefore, collaboration among teachers, parents, and communities is essential. By instilling positive values from an early age, it is expected that the younger generation will grow into well-rounded individuals who are academically competent, socially responsible, and capable of facing future challenges with confidence and integrity.